Motivation, Creativity, and Self-Confidence as Forming Factors of Economic Learning Autonomy - Nafiati, Dewi Amaliah (Fakultas Ekonomi, Universitas Negeri Semarang, 2017)
This research aims to determine the influence of both partial and simultaneous motivation, creativity, and confidence of students in studying to economic subject learning autonomy of the students of Senior High School 4 Tegal. The population in this study was the whole class X Social Education Science which consists of 126 students. The data collection in this research was taken through several methods, whicha are observation, questionnaire, and documentation. The result of this study shows that 77.7% of learning motivation, learning creativity, and self-confidence simultaneously affect the learning autonomy of economics subject of Senior High School 4 Tegal. The results of this study are expected to enable teachers to foster learning motivation, learning creativity and self-confidence of the students in order to form the character of independence. Students are expected to not only rely on the subject matter given by the teachers, but they must be more active and independent in learning to expand a broad insight about economy.